Fluorescence recovery after merging a surfactant-covered droplet a novel technique to measure the diffusion of phospholipid monolayers at fluid/fluid interfaces - Jeong, Dae-Woong (Langmuir : the ACS journal of surfaces and colloids, 2014)
We present a novel technique to measure diffusion coefficients of insoluble surfactant monolayers. We merge a surfactant-coated droplet with a fluorescently labeled planar monolayer. During the merging process, a monolayer on a droplet displaces the existing planar monolayer, leaving a dark area when viewed under a fluorescence microscope. We measure fractional intensities as the dyes recover, which allows diffusion coefficients to be computed. We validate this technique with the two most common phospholipid monolayers (DPPC and DOPC) and study the diffusion of their mixtures. The proposed technique has several advantages over the FRAP technique and is potentially capable of measuring the diffusion of any soluble/insoluble surfactant monolayers